Helping people with psychosis with a low-cost intervention DIALOG+: protocol for the economic evaluation in a randomised control trial in India and Pakistan - Victoria Jane Bird; Sara Evans-Lacko; Lakshmi Venkatraman; Padmavati Ramachandran; Ashar Muhammad Malik; Renata Peppl; Sana Zehra Zehra Sajun; Onaiza Qureshi; Krishna Priya; Hufsa Sarwar (BMJ Open)
Background Approximately 69%–89% of people with severe mental illnesses, particularly psychosis, experience a treatment gap in low- and middle-income countries (LMICs) due to factors such as low public spending on health and weak healthcare systems. The PIECEs project aims to assess the effectiveness and cost-effectiveness of a solution-focused resource-oriented approach (DIALOG+) for improving the quality of life and mental well-being of people with psychosis in India and Pakistan.Methods The research design of this analysis is an economic evaluation piggybacked on the PIECEs randomised control trial to test the feasibility of DIALOG+ in India and Pakistan. It implies a cost-utility analysis with a health system perspective. The costs include the cost of the intervention, the cost of healthcare providers and the cost to the household. The primary outcome will be quality-adjusted life years. Incremental cost, incremental effectiveness and incremental cost-effectiveness ratios will be calculated using linear regression models with a hierarchical data structure. A probabilistic sensitivity analysis will be carried out to test for the uncertainty surrounding the estimates of cost-effectiveness.Discussion This study will provide evidence of a patient-centred approach to improve the quality of community-based care for people with psychosis in India and Pakistan. The economic evaluation will support efforts to scale up low-cost healthcare interventions such as DIALOG+ to rural and unserved areas, which is otherwise challenging in the resource-constrained health systems in many LMICs.Conclusion The evidence on the cost-effectiveness of DIALOG+ will contribute to efforts to improve community-based care and the quality of life for millions of people suffering from mental health problems in India and Pakistan who experience psychosis.Ethics and dissemination This study is approved by the Queen Mary Ethics of Research Committee (UK), Institutional Ethics Committee of SCARF (India), IRD’s Independent Institutional Review Board (IRD_IRB_2021_01_005) (Pakistan), Karawan-e-Hayat Management Committee (Institutional Approval) (Pakistan), Jinnah Postgraduate Medical Centre Research Committee (NO.F.2-81/2021-GENL/60224/JPMC) (Pakistan), Aga Khan’s Ethics Research Committee (2021-5933-17533) (Pakistan) and National Bio-Ethics Committee, Pakistan (Ref: No.4–87/NBC-774/22/2037 Date: 17 May 2022).The findings of this research will be widely disseminated through research publications and engagement with the communities and the healthcare providers in the public and not-for-profit sectors.Trial registration number ISRCTN13022816.